Dynamic characteristics of a convoluted pipe based on euler beam equation using transfer matrix method / Muhamad Norhisham Abdul Ram, Ahmad Azlan Mat Isa and Mohamed Dahalan Mohamed Ramli (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2008)
A numerical technique based on transfer matrix method (TMM) using Euler Beam theory is applied to analyse the dynamic characteristics of a uniform pipe in a convoluted pipe from which the natural frequencies and mode shapes are obtained. Computing code developed based upon transfer matrix method is used to determine the dynamic characteristics. The efficiency of the proposed method is illustrated by comparing the results obtained from NASTRAN software. The results show excellent agreement, which are within approximately below 0.5% for the first five modes. Furthermore the proposed method and computing code can be applied to a more complex structure such as an exhaust system.